2017
DOI: 10.1074/jbc.c116.764043
|View full text |Cite
|
Sign up to set email alerts
|

The GS Protein-coupled A2a Adenosine Receptor Controls T Cell Help in the Germinal Center

Abstract: Edited by Luke O'NeillT follicular helper (T FH ) cells have been shown to be critically required for the germinal center (GC) reaction where B cells undergo class switch recombination and clonal selection to generate high affinity neutralizing antibodies. However, detailed knowledge of the physiological cues within the GC microenvironment that regulate T cell help is limited. The cAMP-elevating, G s protein-coupled A2a adenosine receptor (A2aR) is an evolutionarily conserved receptor that limits and redirects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
(40 reference statements)
2
17
0
Order By: Relevance
“…These observations are consistent with other studies that demonstrated that NP-specific switched memory cells characteristically expressed CD73 [71]. CD11c+ T-bet+ IgM memory cells also exhibit relatively high expression of Adora2a , which encodes a G protein-coupled adenosine receptor of the A2A subtype [72, 73]. Adenosine has been reported to exhibit anti-inflammatory activity [74].…”
Section: Transcriptome Analysessupporting
confidence: 90%
“…These observations are consistent with other studies that demonstrated that NP-specific switched memory cells characteristically expressed CD73 [71]. CD11c+ T-bet+ IgM memory cells also exhibit relatively high expression of Adora2a , which encodes a G protein-coupled adenosine receptor of the A2A subtype [72, 73]. Adenosine has been reported to exhibit anti-inflammatory activity [74].…”
Section: Transcriptome Analysessupporting
confidence: 90%
“…Alternative roles of the A2AR include reducing T cell motility through the modulation of potassium channels [147], regulation of metabolism, and modulation of memory differentiation through PI3K-AKT pathways [9,122,144,[148][149][150]. Although A2AR and A2BR are more highly expressed in effector memory cells their activation is associated with the preservation of a naïve/ central memory phenotype [35].…”
Section: Effect Of Adenosine On T Cell Responsesmentioning
confidence: 99%
“…Investigations in our laboratory and others have recently determined that A2aR signaling during the primary response to a foreign antigen in strong adjuvant has the ability to divert CD4 T cell differentiation away from the follicular helper T (Tfh) and germinal center (GC)–Tfh cell lineages, and consequently could reduce help for the differentiation of antigen‐specific GC B cells and isotype class–switched plasmablasts . In RA, autoreactive B cells are thought to be induced by Tfh cells to undergo clonal expansion, isotype class–switch recombination, and somatic hypermutation within the GCs, and this ultimately leads to the differentiation of anti–citrullinated protein antibody–secreting plasma cells .…”
Section: Introductionmentioning
confidence: 99%